1996
DOI: 10.1055/s-2007-972884
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Fatigue After an Ultra-Marathon Measured as Inspiratory Task Failure

Abstract: Controversial literature exists concerning the occurrence of inspiratory muscle fatigue during efforts performed outside a laboratory. The purpose of this study was to assess inspiratory muscle strength and endurance time measured as Tlim, the length of time a subject can endure a task before the onset of fatigue, in ultra-marathon runners by simple non-invasive techniques before and after an ultra-marathon (87 km). Ten runners, (8 males and 2 females), who had normal clinical evaluation and lung function unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 3 publications
4
34
2
Order By: Relevance
“…The aim of the present study was to apply different noninvasive techniques, commonly used in the literature to detect respiratory muscle fatigue [5, 8, 16], for the measurement of possible impairments of respiratory muscle performance after a type of exercise which was previously shown to induce diaphragmatic fatigue [24]. Also, the authors wanted to compare measures of reduced performance with the published data on reductions in P di,tw.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the present study was to apply different noninvasive techniques, commonly used in the literature to detect respiratory muscle fatigue [5, 8, 16], for the measurement of possible impairments of respiratory muscle performance after a type of exercise which was previously shown to induce diaphragmatic fatigue [24]. Also, the authors wanted to compare measures of reduced performance with the published data on reductions in P di,tw.…”
Section: Discussionmentioning
confidence: 99%
“…FEV1 and mean expiratory flow (MEF) reductions were reported in some of the above mentioned studies [6, 10, 14] while they remained unchanged in others [5, 7, 11, 13, 15]. Finally, K er and S chultz [16] showed that inspiratory muscle endurance time, as measured by sustained inspiratory mouth pressures at a given target pressure and a given duty cycle, was still impaired 3 days after an uotramarathon.…”
mentioning
confidence: 99%
“…Ambiguous results have been observed after ultramarathons. Ker and Schultz () reported no reduction in either maximal inspiratory or expiratory mouth pressures after an ultramarathon (87 km). Warren et al.…”
mentioning
confidence: 99%
“…The decrease in respiratory muscle endurance reported after exercise in both groups of the present study is in agreement with findings in the literature. Loke et al (1982) reported a decrease in MVV after completion of a marathon, Ker and Schultz (1996) noted a decrease in t lim 3 days after completion of an ultra-marathon, and Perret at al. (1999) reported a decrease in t lim after a cycle test to exhaustion.…”
Section: Discussionmentioning
confidence: 94%
“…When the negative pressure inside the cylinder exceeded the predetermined pressure load, the inspiratory orifice situated at the bottom of the cylinder would open, allowing inspiratory flow. The spring adjustment of this valve allowed us to impose 75% of the athlete's P Imax at FRC at each inspiration (Ker and Schultz 1996). The P m , which represented this imposed inspiratory load, was constant for a given adjustment of the threshold valve and was nearly flow-independent once the orifice was open (Johnson et al 1996).…”
Section: Respiratory Muscle Endurancementioning
confidence: 99%